The Sabatier Principle in Electrocatalysis: Basics, Limitations, and Extensions - Ooka, Hideshi; Huang, Jun; Exner, Kai S. (Frontiers in Energy Research, 2021)
The Sabatier principle, which states that the binding energy between the catalyst and the reactant should be neither too strong nor too weak, has been widely used as the key criterion in designing and screening electrocatalytic materials necessary to promote the sustainability of our society. The widespread success of density functional theory (DFT) has made binding energy calculations a routine practice, turning the Sabatier principle from an empirical principle into a quantitative predictive tool. Given its importance in electrocatalysis, we have attempted to introduce the reader to the fundamental concepts of the Sabatier principle with a highlight on the limitations and challenges in its current thermodynamic context. The Sabatier principle is situated at the heart of catalyst development, and moving beyond its current thermodynamic framework is expected to promote the identification of next-generation electrocatalysts.